2014
DOI: 10.1155/2014/938414
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Cutaneous Mucinosis in Dermatomyositis: A Case Report and Review of the Literature

Abstract: We present the case of a patient with dermatomyositis and diffuse cutaneous mucinosis and give an up-to-date detailed review of all the published cases in the English literature describing the demographics, clinical picture, pathology management, and outcomes of this unique group of patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
1
3
0
Order By: Relevance
“…We found that 95% of involved dermatomyositis skin biopsy specimens had at least one of basal vacuolization, mucin, or perivascular inflammation, while 91% had at least one of basal vacuolization or dyskeratotic keratinocytes. These results are similar to literature reports of mucin, basal vacuolization, and perivascular inflammation, including findings from a large study that found vacuolization within 85% of biopsy specimens, mucin within 98% and perivascular inflammation within 94% . Similar to others, we did not find significant overlap between basal vacuolization and mucin (Figure ) .…”
Section: Discussionsupporting
confidence: 91%
“…We found that 95% of involved dermatomyositis skin biopsy specimens had at least one of basal vacuolization, mucin, or perivascular inflammation, while 91% had at least one of basal vacuolization or dyskeratotic keratinocytes. These results are similar to literature reports of mucin, basal vacuolization, and perivascular inflammation, including findings from a large study that found vacuolization within 85% of biopsy specimens, mucin within 98% and perivascular inflammation within 94% . Similar to others, we did not find significant overlap between basal vacuolization and mucin (Figure ) .…”
Section: Discussionsupporting
confidence: 91%
“…However, rarely a secondary form of mucin deposition in a CTD can produce macroscopic deposits of mucin leading to clinical lesions. [15][16][17][18] These clinical mucino-ses are still secondary and must be differentiated from a primary mucinosis in a CTD.…”
Section: Discussionmentioning
confidence: 99%
“…No active cancer was found on full body PET-CT; muscle enzymes were normal; however, MRI showed hyperenhancement of quadriceps muscles bilaterally. The patient did not respond to steroids or methotrexate and required IVIG for symptomatic resolution [ 9 ].…”
Section: Discussionmentioning
confidence: 99%